Stem Cells in Orthopedic Web Information: An Assessment with the DISCERN Tool. (December 2021) - Venosa, Michele; Tarantino, Alessio; Schettini, Irene; Padua, Roberto; Cifone, Maria Grazia; Calvisi, Vittorio; Romanini, Emilio
Objective: Regenerative medicine is experiencing a strong expansion worldwide, including the treatment of some common orthopedic pathologies, with an increase in physicians adopting these technologies. This growing interest has been associated with an equally significant spread of websites dedicated to public information on this topic, often lacking scientific bases. This study aims to evaluate the quality of information on the World Wide Web about stem cells for cartilage disorders in orthopedic practice. Design: On February 19, 2021 we performed a search on Google using as keywords "cartilage stem cells, " considering only the freely accessible sites in Italian, English, French, and Spanish. We selected the first 50 valid results for each language and evaluated them using the DISCERN scale. Results: A total of 249 sites were observed, of which 49 were discarded as duplicates (8) or not relevant to the topic (41). Of the 200 sites surveyed, 47 were affiliated to a singular surgeon (23.5%), 31 to private stakeholders (15.5%), 73 to information sites (36.5%), 8 to public hospitals (4%), 13 to universities (6.5%), and 28 referred to international scientific journals (14%). Only 76 sites (38%) were rated as fair or better, while the remaining 124 (62%) were classified as poor or very poor. Conclusions: The quality of the information promoted for stem cells in orthopedics is generally low, although a significant minority of the sites offers good quality information. A greater commitment on the part of surgeons and other stakeholders is desirable to promote information on regenerative medicine through scientific criteria supported by adequate literature.